The Effect of the Timing of Intramuscular Oxytocin Injection on Maternal Bleeding during the Third Stage of Labour - Sakine Mohamadian; Nahid Jahani shorab; Kobra Mirzakhani (Mashhad University of Medical Sciences, 2013)
Background and aim: The third stage of labour is one of the most troublesome stages of child delivery. The basic principle of the third stage management is administrating prophylactic uterotonics. However, the time of its administration varies in different hospitals. This study aimed to determine the effect of intramuscular oxytocin injection after emergence of the fetal anterior shoulder or placental expulsion on bleeding in the third stage of labour. Methodology: This clinical trial was conducted on 100 pregnant women with gestational age of 38-42 weeks, and singleton pregnancies. Subjects were selected using convenience sampling and were then randomly assigned to intervention (injection of 10 IU intramuscular oxytocin after emergence of the fetal anterior shoulder) and control (injection of 10 IU intramuscular oxytocin after placental expulsion) groups. Blood was collected in containers and weighed with a weighing scale.  A checklist was used to record labor and delivery related data. Data were analyzed by SPSS version 11.5, using Chi-square and t-test. Findings: The mean amount of bleeding during the third stage of labour was 183.4 ± 145.8 and 202.2 ±208.8 ml in intervention and control group, respectively. No significant difference was found between two groups in terms of maternal bleeding. Conclusion: Injection of intramuscular oxytocin either after emergence of the fetal anterior shoulder or placental expulsion does not affect the amount of maternal bleeding during the third stage of labour.